2011
DOI: 10.1007/s10157-011-0530-1
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the duration of nephropathy for achieving clinical remission in patients with IgA nephropathy treated by tonsillectomy and steroid pulse therapy

Abstract: Shorter DN is associated with higher likelihood of clinical remission in IgAN patients treated by TSP therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 37 publications
(66 reference statements)
0
23
0
Order By: Relevance
“…Because of IgA production in tonsillar tissue and the frequent association of symptoms with mucosal infection, in some countries, including China and Japan, tonsillectomy had been reported as an effective treatments to ameliorate clinical symptom in IgAN patients [15,16] Treatment using a combination of tonsillectomy and steroid pulse (TSP) therapy for patients with IgA nephropathy was reported as an effective method in patients to obtain clinical remission (CR) [17,18]. A new long-term study in Japan showed that tonsillectomy was associated with a commendable renal outcome of clinical remission for IgAN patients and delayed renal deterioration even in non-steroid-treated patients [19].…”
Section: Discussionmentioning
confidence: 99%
“…Because of IgA production in tonsillar tissue and the frequent association of symptoms with mucosal infection, in some countries, including China and Japan, tonsillectomy had been reported as an effective treatments to ameliorate clinical symptom in IgAN patients [15,16] Treatment using a combination of tonsillectomy and steroid pulse (TSP) therapy for patients with IgA nephropathy was reported as an effective method in patients to obtain clinical remission (CR) [17,18]. A new long-term study in Japan showed that tonsillectomy was associated with a commendable renal outcome of clinical remission for IgAN patients and delayed renal deterioration even in non-steroid-treated patients [19].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ieiri et al [6] emphasized that a shorter duration from diagnosis until TSP is associated with a high likelihood of CR in IgA nephropathy patients treated with TSP. In our previous study, the comparison between patients who reached CR and those who did not reach CR revealed significant differences in the number of years from diagnosis until TSP ( P  = 0.02), daily proteinuria ( P  < 0.0001), serum creatinine ( P  = 0.006), and pathological grade ( P  = 0.0006).…”
Section: Discussionmentioning
confidence: 99%
“…To the Editor, Suzuki et al [1] showed in their original article that the number of years from diagnosis until tonsillectomy and steroid pulse (TSP) therapy did not influence the clinical remission (CR) rate in IgA nephropathy (IgAN) patients treated with TSP, and they concluded that their results were not in accordance with our previous study [2] which demonstrated that a shorter duration from diagnosis until TSP was associated with a high likelihood of CR in IgAN patients treated with TSP.…”
mentioning
confidence: 86%
“…Our previous study [2] demonstrated that the duration of nephropathy (DN), not the number of years from diagnosis until TSP therapy, was the most veridical predictor of CR as compared with other clinical features such as estimated glomerular filtration rate, age or degree of proteinuria at time of initiation of treatment in IgAN patients treated by TSP therapy. In our study the DN was defined as the period from the first manifestation of hematuria to the initiation of TSP therapy.…”
mentioning
confidence: 99%